2002
DOI: 10.1063/1.1425436
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic defects in ultrafine silicon particles

Abstract: Two defects in the surface oxide layer of ultrafine Si particles, temporarily named an EXL center and an EXH center, were investigated by electron spin resonance (ESR). The Si particles were prepared by a conventional gas evaporation method. The specimens were exposed to air at room temperature to oxidize the surfaces. After the heat treatment in vacuum at 600 and 1000 °C, the ESR signal of the EXL and EXH center appeared, respectively, and after successive annealing in O2 gas at that temperature, the signal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Another defect of relevance for this work is the EX defect, an SiO 2 -associated defect generally observed in Si/ SiO 2 entities after thermal treatment. [51][52][53][54] The observation of part of the 17 Regarding the study on high-/ Si interfaces, convincing results were obtained by ESR on a-ZrO 2 and a-Al 2 O 3 layers grown by atomic layer chemical vapor deposition ͑ALCVD͒ on ͑100͒Si substrates, 10 revealing the presence of Si DB-type centers, P b0 and P b1 . As mentioned above, these defects are the archetypical defects of the Si/ SiO 2 interface, so their presence at the high-/ Si interface would thus herald the presence of a SiO 2͑x͒ -type IL.…”
Section: B Esr Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Another defect of relevance for this work is the EX defect, an SiO 2 -associated defect generally observed in Si/ SiO 2 entities after thermal treatment. [51][52][53][54] The observation of part of the 17 Regarding the study on high-/ Si interfaces, convincing results were obtained by ESR on a-ZrO 2 and a-Al 2 O 3 layers grown by atomic layer chemical vapor deposition ͑ALCVD͒ on ͑100͒Si substrates, 10 revealing the presence of Si DB-type centers, P b0 and P b1 . As mentioned above, these defects are the archetypical defects of the Si/ SiO 2 interface, so their presence at the high-/ Si interface would thus herald the presence of a SiO 2͑x͒ -type IL.…”
Section: B Esr Studiesmentioning
confidence: 89%
“…In this temperature range, one more signal appears at g c = 2.00 251Ϯ 0.00 003, originating from the EXcenter, as ascertained by the observation ͑on optimized spectra-not shown͒ of the typical copresent hyperfine doublet of ϳ16.2 G splitting. [51][52][53][54][55] As stated, the EX defect is an SiO 2 associated center, well-known from studies of the Si/ SiO 2 structure. [51][52][53][54][55] In the as-grown and PGA treated c-Lu 2 O 3 / ͑111͒Si structures no Lu 2 O 3 related paramagnetic point defects could be observed.…”
Section: A C-lu 2 O 3 / "111…simentioning
confidence: 92%
“…In another view, it has been described as an agglomerate of four oxygen-related hole centers ͑OHCs͒. 41 Over the years EX has been observed in a variety of Si/ SiO 2 entities and SiO 2 samples such as oxidized porous Si layers, 41,42 thermally degraded Si/ SiO 2 , 43 silicon nanowires, 44,45 ultrafine silicon particles, 46 fumed silica nanoparticles, 47 and in stacks of nanometer-thick layers of SiO x , Al 2 O 3 , ZrO 2 , and HfO 2 on ͑100͒Si. 16,48,49 Dohi et al suggested the presence of two different variants in ultrafine Si particles, 46 exhibiting the same g value but a different saturation behavior which they labeled EX L and EX H .…”
Section: A P B -Type Interface Defectsmentioning
confidence: 99%
“…41 Over the years EX has been observed in a variety of Si/ SiO 2 entities and SiO 2 samples such as oxidized porous Si layers, 41,42 thermally degraded Si/ SiO 2 , 43 silicon nanowires, 44,45 ultrafine silicon particles, 46 fumed silica nanoparticles, 47 and in stacks of nanometer-thick layers of SiO x , Al 2 O 3 , ZrO 2 , and HfO 2 on ͑100͒Si. 16,48,49 Dohi et al suggested the presence of two different variants in ultrafine Si particles, 46 exhibiting the same g value but a different saturation behavior which they labeled EX L and EX H . This work further suggested that the EX H center observed upon annealing of the particles in vacuum at 900-1000°C is similar to the EX center described above, and that the EX L center observed upon annealing at 600-700°C is identical to the defect reported by Kusumoto and Shoji 50 in Si powders crushed in room ambient which Dohi et al suggest to be related to the Si-OH structure.…”
Section: A P B -Type Interface Defectsmentioning
confidence: 99%
See 1 more Smart Citation